2023
DOI: 10.1002/ddr.22043
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate prevents the migration and invasion, and aerobic glycolysis in gastric cancer via inhibiting Wnt/β‐catenin/c‐Myc signaling

Abstract: Gastric cancer (GC) remains a common cause of cancer death worldwide. Evidence has found that butyrate exhibited antitumor effects on GC cells. However, the mechanism by which butyrate regulate GC cell proliferation, migration, invasion, and aerobic glycolysis remains largely unknown. The proliferation, migration, and invasion of GC cells were tested by EdU staining, transwell assays. Additionally, protein expressions were determined by western blot assay. Next, glucose uptake, lactate production, and cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…In lung cancer, DSTYK silencing enhances glycolysis by the Wnt/β-catenin/LDHA axis [51]. In gastric cancer, LiCl, a Wnt/β-catenin pathway activator, reverses the inhibitory effect of butyrate on aerobic glycolysis [52]. In our study, XAV-939 reversed the increase in GLUT1, HK2, LDHA, and PDK1 expression induced by IL13RA2 overexpression, suggesting that IL13RA2 enhances glycolysis of IH by activating the Wnt/βcatenin pathway.…”
Section: Discussionsupporting
confidence: 53%
“…In lung cancer, DSTYK silencing enhances glycolysis by the Wnt/β-catenin/LDHA axis [51]. In gastric cancer, LiCl, a Wnt/β-catenin pathway activator, reverses the inhibitory effect of butyrate on aerobic glycolysis [52]. In our study, XAV-939 reversed the increase in GLUT1, HK2, LDHA, and PDK1 expression induced by IL13RA2 overexpression, suggesting that IL13RA2 enhances glycolysis of IH by activating the Wnt/βcatenin pathway.…”
Section: Discussionsupporting
confidence: 53%
“…evaluated the anti-tumor effect of butyrate in vitro and in vivo systems. 45 They found that butyrate inhibits proliferation, migration, and invasion of tumor cells. Furthermore, butyrate inhibited aerobic glycolysis in tumor cells via inhibiting wnt/β-catenin/c-Myc signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CD36 has been reported to inhibit the glycolysis and tumorigenesis of CRC through the glypican 4-β-catenin-c-Myc signaling axis (40). Liang et al (41) indicated that butyrate controlled gastric cancer cell proliferation, migration, invasion and aerobic glycolysis by downregulating Wnt/β-catenin/c-MYC signaling. In human hepatocellular carcinoma, Gankyrin has been reported to upregulate glycolysis and glutaminolysis to promote tumorigenesis, metastasis and drug resistance via upregulating c-Myc through the activation of β-catenin signaling (26).…”
Section: Discussionmentioning
confidence: 99%